LEGAL REVIEW RELATING TO CANCELLATION OF ARBITRATION AWARDS THAT ARE ALREADY POWERFUL (INKRACHT) AND FINAL RELATED TO ARBITRATION LAW NO. 30 OF 1999 CONCERNING ARBITRATION CASE STUDY PT. KRAKATAU POSCO AGAINST INDONESIAN NATIONAL ARBITRATION BOARD, DKK AT SERANG STATE COURT - Muchamad Iksan Suryana; Agus Prihartono PS; Anne Gunawati (Universitas Muhammadiyah Tangerang, 2023)
In this thesis, the author discusses the determination of several deviations related to the cancellation of the Arbitration Award as regulated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In this case, the parties and the judges themselves tend to ignore the existence of the Arbitration Institution, the agreement on the absence of an Arbitration Clause is considered a fake document and a deception by the Arbitration Applicant. Krakatau Posco (Arbitration Applicant) against the National Arbitration Board (Arbitration Respondent I) and PT. Krakatau Enggering (Respondent of Arbitration II) in Decision Number 105/Pdt.Arbt/2018/PN.Srg in Serang District Court Class IA. Arbitration clauses are carried out when the contract agreement is about to start between the two parties to avoid disputes before or after in the event of a dispute both parties must file the dispute at the Indonesian National Arbitration Board (BANI). The problems discussed in this thesis are regarding the Determination of Number 105/Pdt.Arbt/2018/PN.Srg. dated September 21, 2018, the judge considered that the absence of the Arbitration Clause was considered a false document and a ruse. The research method used in this thesis is normative juridical through a law approach. The sources used are in the form of secondary legal materials with library techniques that are analyzed qualitatively. The result of this study is the cancellation of the Arbitration decision which was granted by the Panel of Judges at the Serang District Court Class IA based on the fact that there was no Arbitration Clause agreement between the two parties wheKeywords: Arbitration Cancellation, Arbitration Clause